PENGEMBANGAN BAKAT MINAT DAN PENDIDIKAN KARAKTER DI UPTD “KAMPUNG ANAK NEGERI” SURABAYA - Josephine Roosandriantini; Selvia Devy Tiorma (LPPM Unika Widya Karya Malang, 2020)
Abundant natural resources cannot determine the success of a nation in achieving its national goals, but human resources can determine its success. In the times of globalization, Indonesian people really need to develop Human Resources (HR). Thus, character education is needed early on to be able to produce quality human resources to properly support the implementation of development programs. Indonesia often experiences crimes, injustice, corruption, and violence against children, which indirectly shows that our nation is experiencing a character crisis in the society. Therefore, our community service was held in Surabaya's Kampung Anak Negeri (Kanri) because it was necessary to train and develop the character, talent, and interests of the young people from an early age. Our research method is observing and interviewing the people of Kanri so that the community service team could design programs that could beapplied to the children in Kanri. The results of the community service are aimed to optimally develop the potentials, talents, interests, personalities, cooperation, and independence of learners. Keywords: Character, Kanri, Interest, Surabaya